Effect of hygro-thermal treatment in the acoustic characteristics of the wood of Quercus scytophylla Liebm. - Sotomayor-Castellanos, Javier Ramón; Suárez-Béjar, Germán; Olguín-Cerón, Joel Benancio (Instituto de Ecología, A.C., 2015)
The influence of hygro-thermal treatment in the acoustic characteristics of Quercus scytophylla wood was studied. 30 specimens without treatment and 30 with treatment were tested in bending vibration (free-free supported). Density, moisture content, natural frequency, modulus of elasticity in bending vibration, specific modulus, logarithmic decrement, damping coefficient and acoustic coefficient were computed. Statistical analyses demonstrated that natural frequency is a good predictor of the modulus of elasticity and that hygro-thermal treatment modified significantly the density and logarithmic decrement.